Going Global — Remaining Local: Study of the Impact of E-Commerce on Small Retail Firms in Northern India - Kalra, Saurabh (Digital Repository of Theses, 2025)
The rise of online shopping is bringing significant changes to small stores and businesses in Northern India. This shift offers them new possibilities but also creates some considerable difficulties. This study closely examines what helps or hinders these smaller businesses as they attempt to utilise more digital tools and sell online. It examines new online business methods—such as using smartphones for shopping, artificial intelligence, and online payments—impact. At the same time, it acknowledges the serious problems these businesses face, such as poor internet or delivery services, and tough competition from more prominent online companies. The research employed surveys, detailed interviews with business owners, and existing information to gain a comprehensive understanding of this. These findings were analysed using well-known ideas: the Technology Acceptance Model (TAM) and the Diffusion of Innovations (DOI) theory. This study proposes new approaches to considering these theories, particularly for countries like India. The study found that for small businesses to succeed with e-commerce, they need to focus on a few key areas. This includes identifying their niche market segment, providing personalised service to customers, and leveraging government programs such as Digital India and ONDC. Ultimately, this research achieves two primary objectives. First, it provides practical advice and straightforward steps that can help small retailers grow their businesses in a lasting manner, while also contributing to the improvement of government policies for India's rapidly evolving digital landscape. Second, it introduces new ideas to the academic understanding of how businesses in developing countries adopt new technologies.